Նիկոտինոիլ L- պրոլինի հակահիպօքսանտային ազդեցության ուսումնասիրությունը - Աղամալյան, Ի. Հ. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Исследованo влияние никотиноил L-пролина на выживаемость животных в различных экспериментальных моделях гипоксии. Показано, что никотиноил L-пролин в дозе 10 мг/кг в условиях гемической модели гипоксии, вызванной нитритом натрия, проявляет антигипоксическое действие, способствуя увеличению времени выживаемости мышей на 28,53%. The influence of nicotinoil L-proline on the survival rate of animals in various experimental models of hypoxia was studied. It was shown that nicotinoil L-proline at a dose of 10 mg/kg under the conditions of a hemic model of hypoxia caused by sodium nitrite exhibits an antihypoxic effect contributing to an increase in the survival time of mice by 28.53%
Keywords: Փորձարարական և կանխարգելիչ բժշկություն